1992
DOI: 10.1007/bf00866498
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal morphology in children treated by continuous ambulatory peritoneal dialysis

Abstract: Fifty peritoneal biopsies (PB) from 35 patients with end-stage renal disease, treated by continuous ambulatory peritoneal dialysis (CAPD) and aged 2 months to 18 years, were examined by light microscopy (n = 50) and/or scanning electron microscopy. PB were performed during surgical procedures immediately before the start of, during, or after the cessation of CAPD treatment. PB from 15 children without renal disease undergoing laparatomy were examined similarly. Before the start of CAPD, a scarcity and shorteni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…It is proposed that given the association shown by our study between severity and total duration of PD and the previous successful case reports of treatment by peritoneal rest [7,8,13,[23][24][25][26][27][28] that wherever possible, patients should be switched to hemodialysis or transplanted at diagnosis. However, even removing the putative driving force for the disease process by withdrawing PD is not always successful [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that given the association shown by our study between severity and total duration of PD and the previous successful case reports of treatment by peritoneal rest [7,8,13,[23][24][25][26][27][28] that wherever possible, patients should be switched to hemodialysis or transplanted at diagnosis. However, even removing the putative driving force for the disease process by withdrawing PD is not always successful [29].…”
Section: Discussionmentioning
confidence: 99%
“…Mésothélial, interstitial and vascular alterations were described during C A P D thera py. Schneble et al [17] reported that loss o f the mésothé lial layer appeared to be related to prolonged duration o f C A P D treatment, and was independent o f the occurrence o f peritonitis. Since the peritoneum is very vulnerable, however, it is often difficult to distinguish intrinsic lesions from artifacts due to tissue injury during sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular and interstitial changes become more apparent with progressive use of PD, thereby demonstrating a temporal relationship between peritoneal fibrosis, vasculopathy, and time on PD [3]. Peritoneal fibrosis is detected in 50% and 80% of PD patients within one and two years, respectively, on PD [7880]. With regards to mesothelial cells, independent researchers have demonstrated significant changes to these cells following their exposure to PD, which include cell activation, cell hypertrophy, increased vacuolation, partial or complete loss of microvilli, dissolution of cell-cell contacts, and alterations in the number of endoplasmic reticulum and micropinocytotic vesicles [3, 74, 75, 81].…”
Section: Changes To the Peritoneal Membrane During Pd And Peritonitismentioning
confidence: 99%